Characteristic of chronic plaque psoriasis patients treated with biologics in Italy during the COVID-19 Pandemic: Risk analysis from the PSO-BIO-COVID observational study. (1st February 2021) - Talamonti, Marina; Galluzzo, Marco; Chiricozzi, Andrea; Quaglino, Pietro; Fabbrocini, Gabriella; Gisondi, Paolo; Marzano, Angelo Valerio; Potenza, Concetta; Conti, Andrea; Parodi, Aurora; Piaserico, Stefano; Bardazzi, Federico; et al.
ABSTRACT: Background : The susceptibility of patients with chronic plaque psoriasis and the risks or benefits related to the use of biological therapies for COVID-19 are unknown. Few data about prevalence, clinical course and outcomes of COVID-19 among psoriatic patients were reported. The aims of this study were 1) to assess the prevalence and severity of COVID-19 in psoriatic patients treated with biologic agents during the first phase of the emergency (22 February to 22 April 2020) in Italy, and 2) to report the clinical outcomes of patients who have been exposed to individuals with confirmed SARS-CoV-2 infection. Methods : Patients with moderate-to-severe chronic plaque psoriasis, aged ≥18 years and undergoing treatment with biologic agents as of 22 February 2020, were eligible to be included in PSO-BIO-COVID study. Demographic and clinical characteristics of patients using any biologic for psoriasis treatment between 22 February and 22 April 2020 were registered. Results : A total of 12, 807 psoriatic patients were included in the PSO-BIO-COVID study. In this cohort 26 patients (0.2%) had a swab confirmation of SARS-CoV-2 infection. Eleven patients required hospitalization and two died. Conclusion : The incidence of COVID-19 observed in our cohort of psoriatic patients (0.2%) is similar to that seen in the general population (0.31%) in Italy. However, the course of the disease was mild in most patients. Biological therapies may likely lessen 'cytokine storm' of COVID-19, which sometimes lead to multiple organ failure, ARDS, and death.